Analyses of the Updated "Animal rDNA Loci Database" with an Emphasis on Its New Features - Sochorová, Jana; Gálvez, Francisco; Matyášek, Roman; Garcia, Sònia; Kovařík, Aleš (International journal of molecular sciences, 2021)
We report on a major update to the animal rDNA loci database, which now contains cytogenetic information for 45S and 5S rDNA loci in more than 2600 and 1000 species, respectively.The data analyses show the following: (i) A high variability in 5S and 45S loci numbers, with both showing 50-fold or higher variability. However, karyotypes with an extremely high number of loci were rare, and medians generally converged to two 5S sites and two 45S rDNA sites per diploid genome. No relationship was observed between the number of 5S and 45S loci. (ii) The position of 45S rDNA on sex chromosomes was relatively frequent in some groups, particularly in arthropods (14% of karyotypes). Furthermore, 45S rDNA was almost exclusively located in microchromosomes when these were present (in birds and reptiles). (iii) The proportion of active NORs (positively stained with silver staining methods) progressively decreased with an increasing number of 45S rDNA loci, and karyotypes with more than 12 loci showed, on average, less than 40% of active loci. In conclusion, the updated version of the database provides some new insights into the organization of rRNA genes in chromosomes. We expect that its updated content will be useful for taxonomists, comparative cytogeneticists, and evolutionary biologists.&nbsp.
Keywords: ribosomal DNA; databáze genetické; Animals; RNA ribozomální; ribozomální DNA; karyotype; DNA, Ribosomal; karyotypizace; sex chromosome; druhová specificita; Karyotyping; rRNA genes; rDNA; RNA ribozomální 5S; Species Specificity; B chromosome; Evolution, Molecular; karyotyp; molekulární evoluce; Databases, Genetic; Ag-NOR; database; RNA, Ribosomal; RNA, Ribosomal, 5S; Karyotype; zvířata; nucleolar organizer regions; animals